Moral compass or peer influence? examining the drivers of academic honesty in higher education - Usman, Zaiton; Phang, Ing Grace; Jamil, Izaan Aryan Abdul; Krissanya, Nofriska; Mahfirah , Titis Fatarina (Global Advances in Business Studies, 2025)
Academic dishonesty continues to be a pressing issue in higher education, with ethical responsibility and social pressure playing key roles in shaping students' commitment to academic integrity. This study explores the influence of these factors on academic honesty among university students, utilizing partial least squares structural equation modeling (PLS-SEM) to analyze survey responses. Data were collected from 750 university students, with 95% of the responses deemed usable for analysis. The findings reveal that ethical responsibility serves as the strongest determinant of academic honesty, underscoring the pivotal role of intrinsic moral responsibility in ethical decision-making. In contrast, social pressure has a weaker yet statistically significant impact, suggesting that while peer influence affects students' ethical choices, it does not overshadow personal moral convictions. These results align with Rest’s four-component model of moral behavior and social learning theory, reaffirming the combined influence of internal values and external factors on ethical conduct. The study underscores the importance of ethics education, faculty role modelling, and institutional policies in fostering a culture of academic integrity within universities. While positive peer influence can reinforce ethical behavior, interventions should primarily focus on strengthening students’ internal moral responsibility.